2018
DOI: 10.1002/adsu.201800132
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Nitrogen‐Rich Carbon Dots as Fertilizers for Mung Bean Sprouts

Abstract: Nitrogen‐doped carbon‐dots (N‐CDs) are synthesized using a solid‐state method and applied as nanofertilizers. Specifically, 70 g of mung bean seeds are cultivated in the aqueous solution of N‐CDs (0.2 mg mL−1) and yields 646 g of bean sprouts; this yield is significantly higher than that obtained in the pure water control (i.e., 550 g of bean sprouts from 70 g of beans). Furthermore, blue florescence is observed during the sprouting process, which gradually migrates from the beans to the root ends, implying th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…Additionally, CDs enhanced RuBisCO activity and chlorophyll content in the sprouts, suggesting improved photosynthesis [ 80 ]. In another study, V. radiata sprouts were cultivated in the presence of N-doped C-dots (N-CDs) and a significant enhancement in the sprouts’ yield was observed compared to the aqueous control [ 81 ], indicating the effectiveness of N-CDs as a nitrogen nanofertilizer. Qian et al [ 82 ] compared the in planta distribution and the effects of three types of CDs (bared CDs, CD-PEI (modified by polyethylenimine), and CD-PAA (modified by polyacrylic acid)] on growth of C. pepo seedlings.…”
Section: Effects Of Nanomaterials On Seed Germination and Seedlingmentioning
confidence: 99%
“…Additionally, CDs enhanced RuBisCO activity and chlorophyll content in the sprouts, suggesting improved photosynthesis [ 80 ]. In another study, V. radiata sprouts were cultivated in the presence of N-doped C-dots (N-CDs) and a significant enhancement in the sprouts’ yield was observed compared to the aqueous control [ 81 ], indicating the effectiveness of N-CDs as a nitrogen nanofertilizer. Qian et al [ 82 ] compared the in planta distribution and the effects of three types of CDs (bared CDs, CD-PEI (modified by polyethylenimine), and CD-PAA (modified by polyacrylic acid)] on growth of C. pepo seedlings.…”
Section: Effects Of Nanomaterials On Seed Germination and Seedlingmentioning
confidence: 99%
“…Mung bean is the most commonly used plant model in studies due to its fast growing rate. 18,26,33,36,40 Among these studies, CDs played a role in the elongation of root and stem, biomass accumulation, and enhanced the carbohydrates content and photosynthesis (mentioned below) of the mung bean sprouts. For example, Kang et al exposed mung bean sprouts to CDs, in which CDs at 0.02 mg mL À1 were found to improve the root length, stem length, root vigor and single plant fresh weight by 29.9%, 18.3%, 36.1% and 14.9%, respectively (Fig.…”
Section: Enhancement Effectmentioning
confidence: 99%
“…Since then, there have been numerous studies on the effects of CDs on the growth of various plants. Among them, the mung bean, with its rapid growth rate, was the most commonly used model plant in these studies, and the results of CDs in mung bean were usually shown to be promotive [47,53,54] . For example, Zhang et al [53] .…”
Section: Interaction Between Cds and Plantsmentioning
confidence: 99%